1980
DOI: 10.1111/j.1432-1033.1980.tb05984.x
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a New 3‐Oxoacyl‐CoA Thiolase in Rat Liver Peroxisomes

Abstract: A novel 3-oxoacyl-CoA thiolase was found in rat liver. This thiolase, mitochondrial general 3-oxoacyl-CoA thiolase and acetoacetyl-CoA thiolase were purified from the rat liver after the induction of these activities by the administration to rats of di(2-ethylhexyl)phthalate, which enhanced the peroxisomal P-oxidation activity. The new 3-oxoacyl-CoA thiolase was distinguished from mitochondrial and cytoplasmic thiolases by the following : DEAE-cellulose chromatography, phosphocellulose chromatography, immunoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(96 citation statements)
references
References 26 publications
1
95
0
Order By: Relevance
“…The protein content of the supernatant was determined with the Bio-Rad protein assay. Thiolase activity was measured as described previously (19). Briefly, the reaction was initiated by adding tissue samples to a reaction mixture containing 50 M 3-oxooctanoyl-CoA, 0.15 mM CoA, 25 mM MgCl 2 , 50 mM KCl, and 100 mM Tris-HCl (pH 8.0).…”
Section: Measurement Of Thiolase 3-hydroxyacyl-coa Dehydrogenase Anmentioning
confidence: 99%
“…The protein content of the supernatant was determined with the Bio-Rad protein assay. Thiolase activity was measured as described previously (19). Briefly, the reaction was initiated by adding tissue samples to a reaction mixture containing 50 M 3-oxooctanoyl-CoA, 0.15 mM CoA, 25 mM MgCl 2 , 50 mM KCl, and 100 mM Tris-HCl (pH 8.0).…”
Section: Measurement Of Thiolase 3-hydroxyacyl-coa Dehydrogenase Anmentioning
confidence: 99%
“…The mAAT was proved to be immunologically distinct from the mitochondrial acetyl-CoA acyltransferase, from the cytosolic acetyl-CoA acetyltransferase [2] and from the peroxisomal acetyl-CoA acyltransferase [3]. Therefore rocket immunoelectrophoresis can be employed to quantitate the amount of mAAT directly in liver homogenates with purified mAAT as a standard.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that there are two acyl-CoA oxidases with specificity for straight-chain and branched-chain fatty acyl-CoA esters (Vanhove et al 1993). Until recently it was believed that the subsequent steps are catalysed by one bifunctional protein and peroxisomal thiolase (Miyazawa et al 1980), but this view is no longer tenable (see Novikov et al 1994).…”
Section: Short Communicationmentioning
confidence: 99%
“…It is clear that there are two acyl-CoA oxidases with specificity for straight-chain and branched-chain fatty acyl-CoA esters (Vanhove et al 1993). Until recently it was believed that the subsequent steps are catalysed by one bifunctional protein and peroxisomal thiolase (Miyazawa et al 1980), but this view is no longer tenable (see Novikov et al 1994).We have recently found that the bifunctional protein and thiolase as characterized by Hashimoto and coworkers are not involved in pristanic acid β-oxidation. In collaboration with Seedorf and coworkers we have shown that the thiolase encoded by the sterol carrier protein X (SCPx) gene (Seedorf et al 1994) contains 3-ketopristanoyl-CoA thiolase activity, whereas the classical thiolase lacks such activity (Wanders et al 1996).…”
mentioning
confidence: 95%